Nanotechnology Applications in Cancer Therapy: a Physics-Based Approach - Abbas, Benin Amer; Khorshid, Azad Bahaddin; Hussein Hadi, Hussein Hadi; Abd Majid, Haider Najm; Hussein, Hussein Falah (American Journal of Botany and Bioengineering, 2025)
The physicochemical properties of nanoscale materials have not yet been incorporated in the development of current software tools for the simulation of biological systems. However, an integrated package at a computational cost adapted to the scale of this technology does not yet exist. We report a suite of software developed for filling this gap. The suite comprises three primary components: (a) a package for building material configurations and for guiding genetic/protein conjugation; (b) a package for optimizing material parameters with a genetic algorithm; (c) a LAMMPS-based package which computes thermal parameters and diffusion profiles of polymer and heat transmission properties for biological tissues. The implemented computational tools open the possibility to establish guidelines for the rational design of Polimer Curved Patch Antennas (PCPAs) as agents of microwave hyperthermia. The complex dielectric properties of the tumor and three designs of PCPAs injected into the tumor are considered. For the addressed frequency band the third design ensures an improved deep and homogenous temperature distribution.